Pentanuclear Spirocyclic ni4ln Derivatives: Field Induced Slow Magnetic Relaxation in the Dysprosium and Erbium Analogues - Canon-Mancisidor, W; Canon-Mancisidor, W (Wiley-VCH Verlag, 2020)
Five pentanuclear heterometallic isostructural complexes, [Ni4Ln(L)2(LH)2(CH3CN)3Cl]·xH2O·yCH3OH {Ln = YIII (1), GdIII (2), TbIII (3), DyIII (4) and ErIII (5)} [for 1 and 2, x = 2, y = 1; for 3, x = 6, y = 2; for 4, x = 5, y = 1; for 5, x = 2, y = 2] were prepared by the reaction of (E)-2-(hydroxymethyl)-6-{[(2-hydroxyphenyl)imino]methyl}-4-methylphenol (LH3) with LnCl3·6H2O and Ni(OAc)2·4H2O in the presence of tetrabutylammonium hydroxide (TBA-OH) base. The structural characterization reveals that compounds 1–5 contain a spirocyclic pentanuclear core [Ni4Ln(µ3-O)4(µ2-O)4]3+ where two triangular motifs [Ni2Ln(µ3-O)2(µ2-O)2]3+ are fused together through a common vertex of the LnIII ion. The central LnIII ion forms an eight-coordinated distorted triangular dodecahedron geometry, while the nickel(II) ions form a distorted octahedron geometry. Comprehensive dc magnetic studies reveal that antiferromagnetic exchange interaction exists between the NiII centres. The ac susceptibility measurement revels that dysprosium and erbium analogue shows field induced slow magnetic relaxation with an anisotropic barrier (Ueff) of 25.12 cm–1 and 22.13 cm–1 respectively. © 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim